3D Porous Bi2‐xGdxWO6/rGO Composite for Efficient Adsorption‐Enrichment and Photocatalytic Degradation of Organic Dyes. Issue 15 (21st April 2021) - Zhan, Weiwu; Wu, Zhifeng; Tang, Yanren; Ding, Yu; Ma, Cheng; Ding, Xute; Chen, Dianyu
Abstract: Bi 2‐x Gd x WO6 /rGO was prepared by a two‐step process. Firstly, Bi2−x Gdx WO6 (BGWO‐x) nanomaterials were synthesized via a hydrothermal method, and then BGWO‐x was homogenously implanted as a filler into the rGO nanosheets to obtain a novel 3D porous composite. The physical‐chemical properties were investigated by X‐ray diffraction, UV‐vis diffuse reflectance spectroscopy, scanning electron microscopy, transmission electron microscopy, energy dispersive spectrometry, photoluminescence spectroscopy, X‐ray photoelectron spectroscopy and N2 adsorption‐desorption isotherm analysis. The photocatalytic activity of samples was envaulted by degrading three organic dyes (rhodamine B (Rh B), methyl orange (MO), and methylene blue (MB)) under visible‐light irradiation (300 W mercury lamp). Doping of Gd 3+ ions could reduce the bandgap of Bi2 WO6, thus improving its light absorption range. The BGWO‐0.25 with the best photocatalytic performance was selected to construct the BGWO‐0.25/rGO (BGWO/G) nanocomposite, which exhibited the excellent synergistic effect of adsorption‐enrichment and photocatalytic degradation. The removal rates of Rh B, MB, and MO by BGWO/G were about 1.96, 2.94, 2.82 times as that of the pure Bi2 WO6 . And the proposed mechanism of photocatalytic degradation was deduced, in which the photo‐generated O2 .− and h + (active species on the surface of BGWO/G) played the roles of active species during the reaction. Abstract : Gadolinium (Gd) ions could effectively inhibit the recombination of photogenerated electron‐hole pairs through the conversion of Gd 2+ and Gd 3+ . Graphene has a large specific surface area and high carrier mobility, which could effectively absorb organic dyes and accelerate the transfer rate of photogenerated electrons. The synergistic effect of Gd ions and graphene in photocatalysis greatly enhanced the catalytic activity of Bi2 WO6 under visible light.